A study on non-auditory health effects of noise exposure among urban residents of eastern Nepal. - Mishra,Anjali (2018)
ABSTRACT: Background: People are likely to be expose to unwanted noise because of increased traffic along with urbanization. Negative health outcomes like hypertension, annoyance, stress sleep disturbances and mental health effects are associated with noise pollution. Tis study was designed to investigate the association between road traffic noise and non-auditory health effects among urban residents of Eastern Nepal. Methodology: A comparative cross-sectional study enrolled 660 adults(330 residents residing within 100m from the main trunk road and other 330 residents in the side streets) in cities Biratnagar and Ithari. Purposive sampling was used to select the participants. Time-weighted equivalent noise level was estimated using a standard procedure. Pretested semi-structured questionnaire was administered by face-face interview. Height, weight, pulse and blood pressure were also measured. Results: Significant association was seen with depression (p=0.001)anxiety(p=0.007) and stress (p=0.034) among both the groups. Age, gender religion, ethnicity, BM, physical activity and family history of hypertension were the predictors for hypertension. Gender and presence of health problems were significant predictors of depression. Noise exposure, type of house, physical activity and presence of health problems were strong predictor of anxiety. Educational status, exposure to noise at work , presence of health problems and physical activity were predictors of stress. Age, educational status , type of house, ever consumed alcohol, health problems, family history of hypertension were strong predictors of insomnia. Conclusion: High environmental noise levels due to traffic of vehicles were observed. The results of the present study suggests that exposure to road traffic noise associated with depression, anxiety and stress , although, noise exposure was not found to be significantly associated with hypertension and insomnia. this brings us to a conclusion that noise pollution has become a major issue causing adverse health effects and needs to be addressed conclusively by the government of Nepal and protects its citizens. Key words: Common non-auditory health effects, Traffic noise exposure, Urban residents.